Stability assessment of a droop-controlled multi-generator electrical power system in the more electric aircraft using parameter space approach - Gao, Fei; Zheng, Xiancheng; Bozhko, Serhiy (2017)
This paper investigates the dynamic stability of a droop-controlled multi-generator system in the more electric aircraft (MEA). Based on the developed state-space model of the potential dc electrical power system (EPS) architecture, the stability boundaries of EPS operation depending on parameter variations including component parameters and operating conditions are investigated. The effect of multiple parametric uncertainties on EPS stability is graphically illustrated by stability regions maps. In addition, the effect of the droop coefficient on the stability is discussed from the impedance point of view. The detailed mathematical models and analytical results of stability assessment are verified by time domain simulation studies.